Strikebreaking and Intimidation: Mercenaries and Masculinity in Twentieth-Century America - Korneski, Kurt (Labour / Le Travail, 2004)
The article reviews the book, "Strikebreaking and Intimidation: Mercenaries and Masculinity in Twentieth-Century America," by Stephen H. Norwood.